Utilization of Tourism Potential in Improving the Economy in The City of Bontang Region to Support Economic Stability - Afifah Nur Asiah; Endah Nur Amalina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
This study aims to determine themanagement and utilization of Bontang Kuala tourismand its economic impact. This study uses a qualitativeapproach. The informants for this study were the Headof the Bontang City Tourism and Sports Youth Service,the Head of the Tourism Sector, the Head of theDevelopment Section, Tourism Object Development &Creative Economy, Bontang Kuala Village Head,Culinary Business Owners, the community around thetourist attraction, and tourists were determined usingpurposive sampling. Data collection techniques usedare observation, interviews, and documentation. Dataanalysis was carried out through five stages ofactivity, including preparing and organizing data,exploring and coding data, building descriptions,representing and reporting findings, interpretingfindings, and validating the accuracy of conclusions.Well, they start from the provision of facilities andinfrastructure, promotion and marketing strategies, aswell as cooperation with various parties. In addition,Bontang Kuala tourism is also utilized in culturalheritage, nature, and cultural tourism, which has agood impact on the community's economy. Finally,this also affects regional economic stability